STUDENTS’ PERCEPTION OF LECTURERS’ ROLE IN ENHANCING EFL LEARNERS’ COMMUNICATION ABILITY: A STUDY AT EIGHT SEMESTER ON ACADEMIC YEAR 2018 IN IAIN CURUP - Budiman, Wisnu; Apriani, Eka (Universitas Muhammadiyah Semarang, 2019)
The main goal of this study was to investigate about lecturerâ€™s role in teaching speaking for enhancing studentsâ€™ communication ability. The researcher employed descriptive quantitative method which was to know the studentsâ€™ perception on lecturersâ€™ roles to achieve studentsâ€™ communication ability. Then, the researcher chose three lecturers of speaking subject to know about studentsâ€™ perception on lecturersâ€™ roles in enhancing EFL learnersâ€™ communication ability as the purpose of teaching speaking skill. The result shows that the majority of studentsâ€™ perception was in positive category when the lecturers play the various roles in assisting students to improve their communication ability. However, Lecturer â€œAâ€ still need to be more maximize his role as need analyst and Lecturer â€œBâ€ also need to consider his role as manager in teaching speaking, because both of lecturers got neutral perception. Thus, the lecturersâ€™ role is crucial for improving studentsâ€™ communication ability.